2000
DOI: 10.3109/15419060009015004
|View full text |Cite
|
Sign up to set email alerts
|

The CD44 Receptor of Lymphoma Cells: Structure-Function Relationships and Mechanism of Activation

Abstract: Migration of some tumor cells, and their lodgment in target organs, is dependent on the activation of cell surface CD44 receptor, usually detected by its ability to bind hyaluronic acid (HA) or other ligands. In an attempt to reveal the mechanism of tumor cell CD44 activation, we compared the physical and chemical properties of CD44 in nonactivated LB cell lymphoma with those in phorbol 12-myristate 13-acetate (PMA)-activated LB cells and of an LB cell subline (designated HA9) expressing constitutively-active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…PGE 2 has been demonstrated to enhance hyaluronan production by various cell types (34). Glycosylation of cell surface CD44, including the presence of sialic acid residues, seems to decrease hyaluronic acid binding to cells (35). Therefore, if hyaluronan were the sole mediator of the crystal binding effects observed in this study, then one would predict that treatment with PGE 2 , neuraminidase, or tunicamycin might increase crystal binding to cells, whereas the opposite was observed.…”
Section: Discussionmentioning
confidence: 50%
“…PGE 2 has been demonstrated to enhance hyaluronan production by various cell types (34). Glycosylation of cell surface CD44, including the presence of sialic acid residues, seems to decrease hyaluronic acid binding to cells (35). Therefore, if hyaluronan were the sole mediator of the crystal binding effects observed in this study, then one would predict that treatment with PGE 2 , neuraminidase, or tunicamycin might increase crystal binding to cells, whereas the opposite was observed.…”
Section: Discussionmentioning
confidence: 50%
“…24,[34][35][36][37][38] Indeed, flow cytometric analysis revealed that the majority of thymocytes and …”
Section: Clonal Expansion and Peripheral Infiltration Of Activated Ptmentioning
confidence: 99%
“…To determine this, recipients received the tolerogenic regimen along with mAbs to the VLA-4␣ (CD49d) integrin, responsible for homing to vascular and lymphatic endothelium, through binding to its ligands fibronectin, VCAM-1, and mucosal addressin cell adhesion molecule-1 (30,31), or mAbs to CD44, the mucin receptor, responsible for homing to endothelium (32). The results (Fig.…”
Section: Anti-cd62l Mab Prevents Tolerance Induction and Has No Costimentioning
confidence: 99%